2018
DOI: 10.20944/preprints201805.0429.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Similarity of the Action of Franklin and ESE Lightning Rods under Natural Conditions

Abstract: In the lightning rods categorized as ESE an intermittent voltage impulse is applied to the lightning rod to modulate the electric field at its tip in an attempt to speed up the initiation of a connecting leader from the lightning rod when it is under the influence of a down coming stepped leader. In this paper it is shown that due to the stepping nature of the down coming stepped leader, there is a natural modulation of the electric field at the tip of any lightning rod exposed to the lightning stepped leaders… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…(d) Additionally, the proposed NPAP is promising for potential applications involving lightning rods [11]- [13], [46], surge arresters with parallel gaps [47], and other similar devices [48]- [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(d) Additionally, the proposed NPAP is promising for potential applications involving lightning rods [11]- [13], [46], surge arresters with parallel gaps [47], and other similar devices [48]- [51].…”
Section: Discussionmentioning
confidence: 99%
“…The literature [12] has also provided a novel experimental technique with which to prove the effectiveness of an early streamer emission air terminal versus a traditional Franklin rod in a laboratory, and researchers have found that the peak value of active rod charge is almost twice as high as that of the charge of a conventional Franklin rod, and that the induction element plays a significant role in the development of this phenomenon. Previous literature [13] has also compared the similarity of the action of conventional and ESE lightning rods under natural conditions, and the conclusion suggests that there should be no obvious difference between ESE and conventional lightning rods. However, the main differences between the early streamer emission method and the proposed PFA guiding method lie in their applications, working scenarios, and conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-A high voltage pulses that are being generated at the tip of the ESE lightning rods will be produced by a stepped leader at any standard Franklin rod. Because of that ESE rods have the same protection radius as the standard Franklin rods [15].…”
Section: Criticism Of the Eseatsmentioning
confidence: 99%